2017
DOI: 10.24251/hicss.2017.241
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Valuation of Location Privacy: a Crowdsourcing-Based Approach

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Smith, et al [23] give an interdisciplinary review of privacy-related research. Most of the prior literature focus on privacy concerns of information collected online [22,9,6] and location-based privacy [31,29,19]. In addition, Xu et al [29] extended the privacy calculus model by including personality characteristics (previous privacy experience, coupon proneness, and personal innovativeness) and different methods of personalization (covert and overt) for locationaware marketing.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Smith, et al [23] give an interdisciplinary review of privacy-related research. Most of the prior literature focus on privacy concerns of information collected online [22,9,6] and location-based privacy [31,29,19]. In addition, Xu et al [29] extended the privacy calculus model by including personality characteristics (previous privacy experience, coupon proneness, and personal innovativeness) and different methods of personalization (covert and overt) for locationaware marketing.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Many studies have shown that privacy concerns affect behavioral intentions like intent to adopt and intent to use [31,22,14,26,19]. According to the APCO model, privacy concerns negatively influence behavioral intentions.…”
Section: Behavioral Intentionsmentioning
confidence: 99%
“…Former studies of the privacy field have used crowdsourcing methodologies to investigate different privacy aspects, including users' valuations of location privacy [47], users' privacy expectations of mobile apps [36] and crowdsourced recommendation system development for privacy protection settings used in popular apps [2]. For our purposes we recruited adult participants via AMT.…”
Section: Recruitmentmentioning
confidence: 99%
“…Over-stepping users' expectations of privacy can be costly. Surprising users by sharing their data with unexpected people and organizations or using data in unexpected ways can deter users from using a system [21,36] or push them to choose other alternatives [19,47]. Privacy-by-design (PbD) initiatives propose a design and development framework that aids in the production of privacy-respectful systems [10,34].…”
Section: Introductionmentioning
confidence: 99%
“…Dobson and Fisher [48] see this as a kind of new panopticon ("panopticon III") in which, for the first time, benefits are available both for the watchers and those that are being watched. We allow the creation of the big spatial datasets that are the result of the big "data grab" [49] for a multitude of reasons, seemingly without much thought and hesitation and even when users are not visibly compensated for relinquishing their location privacy [50]. Behavior such as this is consistent with the way software functions are perceived-they hide from our conscious thoughts, retreating into the background hum of the ever-present technology and become visible only in its brief moments of failure [51,52].…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%